2007
DOI: 10.1038/sj.ejcn.1602844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc supplementation on vitamin status of middle-aged and older European adults: the ZENITH study

Abstract: Objective: To assess the effects of zinc supplementation on vitamin status in middle-aged and older volunteers. Subjects/Methods: Three hundred and eighty-seven healthy middle-aged (55-70 years) and older (70-85 years) men and women, randomly allocated to three groups to receive 15 or 30 mg Zn/day or placebo for 6 months. Dietary intake was assessed by means of a validated 4-day recall record. Fasting blood samples were simultaneously analysed for levels of plasma retinol and a-tocopherol by high-performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Finally, a trial of middle and older‐aged men found that long‐term zinc supplementation (i.e. for 6‐months) was associated with increased plasma vitamin A levels (for 30 mg of zinc daily; P < 0.0001) .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a trial of middle and older‐aged men found that long‐term zinc supplementation (i.e. for 6‐months) was associated with increased plasma vitamin A levels (for 30 mg of zinc daily; P < 0.0001) .…”
Section: Resultsmentioning
confidence: 99%
“…The explanation for this relative preservation of β-carotene in the face of retinol deficiency is not known. Possible explanations, none of which we were able to assess in this study, include a plant-based diet, which has been shown to have a significant impact on β-carotene serum levels but no significant effect on retinol levels (40, 41), the presence of another deficiency, such as zinc, that negatively affects retinol mobilization from the liver (42) or the negative impact of the acute phase response on retinol levels as has been shown in children with malaria (43), and in HIV-1 seropositive subjects (44). …”
Section: Discussionmentioning
confidence: 98%
“…Low zinc status increases vitamin E requirement due to decreased intestinal absorption. Whereas this low or marginal zinc status also decreases folate absorption from food [44]. The decreased gustatory sense which strongly affects the food intake among the elderly is also due to zinc deficiencies [16].…”
Section: Zincmentioning
confidence: 99%